Akuntabilitas Pengelolaan Dana Desa di Desa Budugsidorejo Kabupaten Jombang Tahun 2015 - Setiawan, Andi; Haboddin, Muhtar; Wilujeng, Nila Febri (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
This study describes the accountability of the management of village fund allocation (ADD) in the village Budugsidorejo Sumobito District of Jombang in 2015. The aim of this study is to describe and explain the presence or absence of accountability in the management of ADD in 2015. The theory that formed the basis of looking at accountability ADD is Rahardjo Adisasmito concept of accountability by which to see accountability in financial management can be seen from the indicators of financial accountability, accountability benefits and procedural accountability. This study uses qualitative descriptive method and determination of informants by using purposive sampling technique. The results of this study indicate that accountability in the management of ADD are in accordance with the applicable procedures and can be realized because of the internal and external oversight. Given such surveillance raises their awareness that the programs funded from ADD should be accounted for as well as possible.